2009
DOI: 10.7146/math.scand.a-15113
|View full text |Cite
|
Sign up to set email alerts
|

On the spectrum of the generalized Gelfand pair $(u(p,q), h_{n})$, $p+q=n$

Abstract: It is known that the spectrum of the Gelfand pair $(U(n), H_{n})$ is homeomorphic to the Heisenberg fan. In this paper after defining a suitable notion of spectrum, we prove an analogous result for the generalized Gelfand pair $(U(p,q), H_{n})$, $p+q=n$.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Since hepatotoxicity is one of the main reasons for drugs to be retracted from the market, a reliable platform for pre-clinical liver toxicity screening is an ideal tool to reduce costs. The human HepaRG® lines an attractive tool for a first quick screening of new chemical entities 32,33 . The HepaRG® cell line is derived from a human hepatocarcinoma.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Since hepatotoxicity is one of the main reasons for drugs to be retracted from the market, a reliable platform for pre-clinical liver toxicity screening is an ideal tool to reduce costs. The human HepaRG® lines an attractive tool for a first quick screening of new chemical entities 32,33 . The HepaRG® cell line is derived from a human hepatocarcinoma.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…As a result, concentration gradients of substances (growth factors, metabolites, and oxygen) are formed, which are dissolved in the blood or secreted by the overlying periportal hepatocytes [34]. The gradient is determined by changes in the composition of blood plasma and oxygenation differences in the bloodstream of the area between the periportal and perivenous zones [35]. The phenomenon of hepatocyte heterogeneity has been studied in many works [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The gradient is determined by changes in the composition of blood plasma and oxygenation differences in the bloodstream of the area between the periportal and perivenous zones [35]. The phenomenon of hepatocyte heterogeneity has been studied in many works [34][35][36][37][38]. It was shown that hepatocytes located in the periportal zone (zone 1) specialize in gluconeogenesis and β-oxidation, while glycolysis, lipogenesis, and detoxification processes of high intensity were detected in hepatocytes located around the central vein (zone 3).…”
Section: Discussionmentioning
confidence: 99%